الوسواس القهري وأحكامه في الفقه الإسلامي-نماذج تطبيقية مختارة - بكري, مريم; حاقة, أنفال (University of Eloued-جامعة الوادي, 2022)
" هذه الدِّراسة الموسومة بـ: ""الوسواس القهري وأحكامه في الفقه الإسلامي-نماذج تطبيقية مختارة"" والتي كان الإشكال الرئيس الذي تسعى للإجابة عنه هو: ماهي الأحكام الفقهية المتعلقة بمرضى الوسواس القهري؟ أجابت الدراسة عن ذلك من خلال ثلاثة مباحث: خصّصت الأول للتعريف بالوسواس القهري أنواعه وأسبابه، والثاني تطرقت فيه إلى المسائل الفقهية المتعلقة بمرضى الوسواس القهري في باب الطهارة، ثم بيّنت في الثالث المسائل الفقهية المتعلقة بمرضى الوسواس القهري في غير باب الطهارة. وقد توصلت الدراسة غلى جملة من النتائج أهمها: أنّ الوسواس القهري هو اضطراب مرضي، له أسبابه المهيئة له، وينتج عنه إكتئاب وإنعزال يتوجب على المصاب به زيارة طبيب نفسي، وأيضا أنّ الشريعة الإسلامية اهتمت بمرضى الوسواس القهري وراعت الضرر الناتج عنه.""This study is tagged with:""Obsessive Compulsive Disorder and its provisions in Islamic jurisprudence- selected applied models"", was the main problem you are seeking to answer: what are the jurisprudence provisions concerning OCD patients? The study answered this through three investigations: the first was devoted to the definition of obsessive compulsive disorder its types and causes, and the second touched on the jurisprudence Issues concerning OCD patients in bab al-Tahara, and then in the third it showed the jurisprudence Issues concerning OCD patients in the non-purity section. The study found a number of results, the most important of which is that obsessive compulsive disorder is a pathological disorder, with its causes prepared for it, and results in depression and isolation, the patient must visit a psychiatrist, and also that Islamic law cared for OCD patients and took care of the damage caused. "
مذكرة ماستر
Keywords: الوسواس القهري، أحكام، فقه، الشريعة، الطب النفسي; Obsessive-compulsive disorder, rulings, jurisprudence, Sharia, psychiatry